2015
DOI: 10.1111/irfi.12057
|View full text |Cite
|
Sign up to set email alerts
|

Convertible Debt: Financing Decisions and Voluntary Conversion under Ambiguity

Abstract: Abstract. This paper integrates ambiguity into a contingent claim model for convertible debt. We study how convertible debt valuation is affected by the ambiguity biases of equity holders and debt holders and provide sensitivity analysis of the bond value to changes in attitude toward ambiguity, firm and bond parameters. Our results, which are summarized into six main predictions, are consistent with recent empirical evidence and offer a possible interpretation of some corporate finance puzzles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Previous studies found managers are more likely to increase cash holding for the ambiguous future ( Neamtiu et al, 2014 ; Agliardi et al, 2015 ; Breuer, 2017 ; Nishimura and Ozaki, 2017 , etc.) Similarly, our results show the negative influence of ambiguity on cash holding policy.…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found managers are more likely to increase cash holding for the ambiguous future ( Neamtiu et al, 2014 ; Agliardi et al, 2015 ; Breuer, 2017 ; Nishimura and Ozaki, 2017 , etc.) Similarly, our results show the negative influence of ambiguity on cash holding policy.…”
Section: Empirical Analysismentioning
confidence: 99%
“…One issue that contributes to the fuzzy picture of dividend policy and hinders the elaboration of new perspectives is the assumption that people are always rational and will pursue the maximization of personal profits. The rising studies consider behavioral biases in modeling complex decision-making processes ( Agliardi et al, 2015 ). Baker and Wurgler (2004) point out investors’ trading behavior positively respond to dividend payouts, so managers tend to cater to investors for obtaining stock premiums (also see Li and Lie, 2006 ; Ferris et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally this prediction is based on probabilistic models. Recently, Agliardi et al (2015) introduce ambiguity into a model for convertible debt. From their theoretical model, we deduce that the call delay increases for firms with higher ambiguity aversion or in periods of higher ambiguity.…”
Section: The Financial Distress and Transaction Costs Hypothesismentioning
confidence: 99%
“…Our NMEU utility evaluates and combines the worst case in negotiators' minds with the standard probabilistic case. Separating risk from uncertainty (Ellsberg, 1961;Abdellaoui et al, 2015;Agliardi et al, 2015), we present conditions for negotiation agreement under ambiguity and incorporate negotiators' aversion to uncertainty and network position in the real options analysis to show how they affect investment outcomes and optimal agreement 2 . We deliberately do not investigate or discuss the role of risk aversion in the real options dynamics since these effects have been well documented in the literature (see e.g.…”
Section: Introductionmentioning
confidence: 99%